ORAL MYTH OF BADAWANGNALA IN THE ISLAND OF SERANGAN, SOUTH DENPASAR - Soedjiwo, Novena Ade Fredyarini; Suarka, I Nyoman; Weda Kusuma, I Nyoman; Rai Putra, Ida Bagus (e-Journal of Linguistics; 2016: Vol 10. No. 1 January, 2016)
The myth of Badawanganala believed by the people of Bali is found on Lontar Adiparwa, but in Serangan Island it has its own version, adapted to the present context. With the global influence, the local culture is slowly eroding, as in Serangan Island, namely reclamation. Reclamation occurred in 1994, causing changes in the life cycle both on land and sea; the marine life was damaged, due to the greed of rulers. Badawangnala myth, constructed in Pura Batu Api is believed to neutralize and reconstruct patterns of harmonious and prosperous behavior. The research objective is to understand the meaning and function of Badawanganala oral myth in Serangan Island. The theory used in this research includes the narrative discourse theory, the theory of mythology, transformation theory, and the theory of semiotics. The research method is qualitative with qualitative and interpretative descriptive analysis techniques. The primary data are taken from informants purposively and the secondary data are from the study of documents. The collecting of data is done through observation, interviews and document study. The structural analysis of the text is started from the text of the Bedawangnala myth of Adiparwa then Medang Kemulan, and the text spoken by indigenous leaders, bendesa adat of Serangan. The text is associated with linguistic intrinsic elements that build up the myth of Badawangnala in Serangan Island particularly on its characterizations The research findings are strengthening of the cultural attitudes and behaviors of the Serangan community to defend their rights, and the younger generations are able to promote solidarity through ritual, that is odalan (temple ceremony), and Batu Api Temple is the implementation of strength and confidence in the ritual policy.
Keywords: Bedawangnala myth, meaning, and function